Lubricating coating for alloy wire surface and preparation method thereof

By modifying the silicone resin and Mo-Si-B-Sm alloy powder composite material, a high cross-linking density network and dense stacking layer are constructed, which solves the high temperature resistance and corrosion resistance problems of the lubricating coating of high-temperature alloy fasteners and improves the wear resistance and oxidation resistance of the coating.

CN120699535AActive Publication Date: 2025-09-26SHENYANG HANGDA TECH LLC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511166800.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-20
Publication Date
2025-09-26
Estimated Expiration
2045-08-20

AI Technical Summary

Technical Problem

Existing lubricating coatings are prone to decomposition, brittle fracture, and oxidation failure during the hot upsetting process of high-temperature alloy fasteners, resulting in product adhesion, mold wear, and material damage, making it difficult to simultaneously meet high-temperature resistance and corrosion resistance.

Method used

A composite material of modified silicone resin and Mo-Si-B-Sm alloy powder is used. A high-crosslinking density network structure and a dense stacking layer are constructed through a silicone-boron nitride hybrid crosslinking network and Mo-Si-B-Sm-based anti-corrosion filler. Combined with the lubricating properties of molybdenum disulfide and NiFe2O4, a high-temperature resistant and antioxidant lubricating coating is formed.

Benefits of technology

Significantly improve the wear resistance, mechanical properties and high-temperature corrosion resistance of the coating, extend the life of the mold, and improve production efficiency and product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120699535A_ABST
    Figure CN120699535A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lubricating coatings, and particularly relates to a lubricating coating for the surface of an alloy wire and a preparation method of the lubricating coating. The invention relates to a lubricating coating for the surface of an alloy wire. The lubricating coating is prepared from the following raw materials in percentage by weight: 13-17% of modified organic silicon resin, 5-8% of molybdenum disulfide, 2-4% of NiFe2O4, 5-8% of anticorrosive filler, 2-3% of thixotropic agent, 1.5-2% of dispersing agent, 0.5-1% of flatting agent and the balance of solvent. The modified organic silicon resin prepared through an organic silicon-boron nitride hybrid cross-linked network has excellent high-temperature resistance (gt, 800 DEG C), the wear resistance and mechanical properties of a coating can be remarkably improved, and the high-temperature oxidation corrosion resistance of the coating can be improved by adding the Mo-Si-B-Sm-based anti-corrosion filler.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lubricating coatings, and particularly relates to a lubricating coating for the surface of an alloy wire and a preparation method thereof. Background Art

[0002] During the hot upsetting of high-temperature alloy fasteners, processing temperatures reach as high as 600-1000°C, accompanied by extreme forging pressures. Fastener protective coatings must not only exhibit excellent high-temperature resistance but also possess excellent impact resistance, toughness, and corrosion resistance. Existing lubricating coatings face the following technical challenges: Traditional polymer matrices are susceptible to decomposition and carbonization at high temperatures, leading to structural damage in the coating; inorganic fillers exhibit weak interfacial bonding with the matrix, prone to brittle fracture under dynamic loads; commonly used solid lubricants such as molybdenum disulfide and graphite oxidatively fail under high-temperature and high-pressure environments, losing their lubricating properties. More critically, the coating's reduced density at high temperatures accelerates oxidative corrosion of the matrix, and traditional anti-corrosion fillers struggle to maintain structural stability under extreme temperatures. The combination of these issues not only leads to severe adhesion between the product and the mold, compromising demolding and production continuity, but also causes rapid mold wear and surface damage, directly impacting product quality and production efficiency. Therefore, developing a lubricating coating that simultaneously meets both high-temperature and corrosion resistance requirements is a key technological breakthrough for improving the quality of hot upsetting of high-temperature alloy fasteners. Summary of the Invention

[0003] The first object of the present invention is to provide a lubricating coating for the surface of an alloy wire, which has excellent mechanical properties and outstanding high-temperature corrosion resistance.

[0004] The second object of the present invention is to provide a method for preparing the above-mentioned silicon-carbon composite negative electrode material.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is: A lubricating coating for the surface of an alloy wire, comprising the following raw materials in percentage by weight: 13-17% modified silicone resin, 5-8% molybdenum disulfide, 2-4% NiFe2O4, 5-8% anti-corrosion filler, 2-3% thixotropic agent, 1.5-2% dispersant, 0.5-1% leveling agent, and the balance being solvent; The modified silicone resin is prepared by the following preparation process: (1) Add 1,3-dimethoxy-1,3-dimethyl-1,3-divinyldisiloxane and hydroxylated boron nitride to an ethanol aqueous solution, stir to react, filter, wash, and dry to obtain intermediate 1; (2) In an inert gas atmosphere, polymethylsilane and intermediate 1 are added to anhydrous toluene, heated for reaction, and after completion of the reaction, the modified silicone resin is obtained by distillation under reduced pressure.

[0006] Furthermore, the structural formula of the intermediate 1 in step (1) is .

[0007] Furthermore, in step (1), the mass ratio of 1,3-dimethoxy-1,3-dimethyl-1,3-divinyldisiloxane to hydroxylated boron nitride is 1:(6-8); the temperature of the stirring reaction is 60-80° C., and the time is 4-6 hours.

[0008] Furthermore, in step (1), the dosage ratio of the 1,3-dimethoxy-1,3-dimethyl-1,3-divinyldisiloxane to the ethanol aqueous solution is 1 g: (200-250) mL; and the volume ratio of ethanol to water in the ethanol aqueous solution is 9:1.

[0009] Furthermore, in step (2), the mass ratio of the intermediate 1 to polymethylsilane is 1:(1.5-2); the temperature of the heating reaction is 110-130° C., and the time is 2-4 hours.

[0010] Furthermore, in step (2), the ratio of the intermediate 1 to anhydrous toluene is 1 g: (100-120) mL.

[0011] Furthermore, the anti-corrosion filler is prepared by the following preparation process: (a) Molybdenum powder, silicon powder, boron powder, and samarium powder are ball-milled in an inert gas atmosphere to obtain alloy powder. The alloy powder is pressure-sintered in a vacuum, depressurized, maintained, and cooled to obtain Mo-Si-B-Sm alloy powder; (b) grinding the surface of the Mo-Si-B-Sm alloy powder, sandblasting, ultrasonic cleaning, and drying to obtain treated Mo-Si-B-Sm alloy powder; (c) adding dopamine hydrochloride and Al2O3 nanosheets to a Tris-HCl buffer solution and ultrasonically dispersing the mixture to obtain a mixed solution, immersing the treated Mo-Si-B-Sm alloy powder in the mixed solution, stirring, centrifuging, washing, drying, and then annealing in an argon atmosphere to obtain the anti-corrosion filler.

[0012] Furthermore, the mass ratio of molybdenum powder, silicon powder, boron powder and samarium powder in step (a) is (90-97): (2-5): (0.5-2): (0.5-3); the pressure sintering temperature is 1400-1600°C, the pressure is 30-50 MPa, and the time is 2-5 hours; the pressure reduction and heat preservation temperature is 1700-1800°C, the pressure is 10-20 MPa, and the time is 2-3 hours.

[0013] Furthermore, the air flow pressure of the sandblasting treatment in step (b) is 0.5-0.8 MPa, and the time is 10-15 s; the mass ratio of Al2O3 nanosheets to dopamine hydrochloride in step (c) is 1:(1-1.2); the amount ratio of the treated Mo-Si-B-Sm alloy powder to the mixed solution is 1 g:100-150 mL; the annealing temperature is 300-350 ° C, and the time is 1-1.5 h.

[0014] Furthermore, the concentration of the Tris-HCl buffer is 0.2 mol / L; the usage ratio of the Al2O3 nanosheets to the Tris-HCl buffer is 1 g: (2-2.5) mL.

[0015] Furthermore, the thixotropic agent is any one of wax slurry, bentonite or BYK320; the leveling agent is BYK354 or BYK300; the dispersant is BYK110; and the solvent is a mixed solution of ethanol and isopropyl alcohol.

[0016] Furthermore, the solvent is a mixed solution of ethanol and isopropanol in a volume ratio of 7:3.

[0017] The method for preparing the lubricating coating for the surface of the alloy wire comprises the following steps: According to the weight percentage, the modified silicone resin is added to 50-60% of the solvent mass and stirred to form a resin solution, and then molybdenum disulfide, NiFe2O4 and anti-corrosion filler are added in sequence. After stirring, a thixotropic agent, a dispersant BYK110 and the remaining solvent are added, and finally a leveling agent is added and stirred to prepare the lubricating coating.

[0018] The beneficial technical effects of the present invention are: 1. The modified silicone resin prepared through a silicone-boron nitride hybrid cross-linked network exhibits excellent high-temperature resistance (>800°C) and can significantly enhance the wear resistance and mechanical properties of the coating. Using high-temperature-resistant hydroxylated boron nitride as a raw material, the present invention utilizes the condensation reaction of its surface hydroxyl groups with 1,3-dimethoxy-1,3-dimethyl-1,3-divinyldisiloxane to form stable Si-O-B covalent bonds and introduce active double bonds. This allows the h-BN to be uniformly dispersed and anchored within the polymer network, imparting high-temperature resistance to the resin while avoiding interfacial defects caused by filler agglomeration. The introduced double bonds then undergo a hydrosilylation reaction with the Si-H bonds in polymethylsilane to construct a high-crosslinking density network structure. The resulting flexible Si-CH2-CH2-Si segments, combined with Si-O-Si chains, improve the mechanical and wear resistance of the coating. Under dynamic loads, the flexible segments absorb friction energy through conformational changes, while the interlayer slip effect of the h-BN nanosheets further dissipates stress, effectively inhibiting crack initiation and propagation.

[0019] 2. The present invention also adds a Mo-Si-B-Sm-based anti-corrosion filler, which can improve the high-temperature oxidation corrosion resistance of the coating. The present invention adds the rare earth element Sm to the Mo-Si-B alloy. The addition of Sm further refines the grain size and increases the material density. Sm generates Sm2O3 during high-temperature oxidation, forming a Sm-Si-BO composite glass phase with SiO2 / B2O3, which can effectively block oxygen diffusion. After multi-stage grinding and sandblasting, the Mo-Si-B-Sm alloy powder forms a uniform rough morphology on the surface, significantly increasing the specific surface area and the number of active sites. Then, through the in-situ polymerization reaction of polydopamine, Al2O3 nanosheets adhere to form a densely packed continuous layer, which can effectively block the penetration of corrosive media and delay chemical corrosion of the substrate.

[0020] 3. The present invention uses molybdenum disulfide and NiFe2O4 as lubricating fillers. Molybdenum disulfide has lubricating properties in the low-temperature range (<300°C), and NiFe2O4 has excellent oxidation stability and can take over the lubrication function after molybdenum disulfide fails. At high temperatures, the metal ions in the spinel crystal structure undergo reversible displacement. This crystal slip phenomenon can form a lubricating transfer film on the contact surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the infrared characterization image of the intermediate 1 and the modified silicone resin in Example 1 of the present invention. DETAILED DESCRIPTION

[0022] The following is a further detailed description of the present invention in conjunction with specific preferred embodiments, and it is not intended that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art of the present invention, without departing from the inventive concept, several simple deductions or replacements can also be made, all of which should be considered to belong to the scope of protection of the present invention. The specific conditions not indicated in the examples are carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0023] The preparation process of the polymethylsilane of the present invention comprises the following steps: cutting a sodium metal block into sodium particles with a particle size of less than 2 mm in dry THF; adding 10 g of the sodium particles to 250 mL of toluene under a dry nitrogen atmosphere; then dropwise adding 22 mL of monomeric dichloromethylsilane; and subjecting the mixture to a reflux reaction for 10-12 hours; cooling the mixture to room temperature after completion of the reaction, filtering the mixture, and removing toluene from the filtrate by vacuum distillation to obtain the polymethylsilane; the weight-average molecular weight of the polymethylsilane is 1820.

[0024] The preparation process of the hydroxylated boron nitride of the present invention is as follows: 1 g of hexagonal boron nitride (specification: 100 nm) is added to 30 mL of sodium hydroxide solution (1 mol / L), stirred at 110° C. for 10 h, filtered, rinsed with deionized water, and dried to obtain the hydroxylated boron nitride.

[0025] (1) Implementation Example 1: Example 1 provides a lubricating coating for the surface of an alloy wire, comprising the following raw materials in percentage by weight: 15% modified silicone resin, 6% molybdenum disulfide, 3% NiFe2O4, 6% anti-corrosion filler, 2% wax slurry, 1.5% BYK110, 0.8% BYK354, and the balance being a solvent prepared by mixing ethanol and isopropanol in a volume ratio of 7:3; The modified silicone resin is prepared by the following preparation process: (1) 1,3-dimethoxy-1,3-dimethyl-1,3-divinyldisiloxane and hydroxylated boron nitride were added to an ethanol aqueous solution with a volume ratio of ethanol to water of 9:1, according to the ratio of 1 g:7 g:200 mL of 1,3-dimethoxy-1,3-dimethyl-1,3-divinyldisiloxane, hydroxylated boron nitride and ethanol aqueous solution. The mixture was stirred at 70°C for 5 h, filtered, washed and dried to obtain intermediate 1.

[0026] (2) Under nitrogen atmosphere, intermediate 1 and polymethylsilane were added to anhydrous toluene in a ratio of 1 g:1.8 g:100 mL, and the mixture was reacted at 120°C for 3 h. After the reaction, the modified silicone resin was obtained by vacuum distillation.

[0027] The infrared characterization of the intermediate 1 and the modified silicone resin is as follows: Figure 1 As shown by Figure 1 It can be seen that compared with hydroxylated boron nitride, intermediate 1 has a -1 , 1600cm -1 The characteristic peak of -CH=CH2 appears at 1010-950cm -1 corresponds to SiCH=CH2, 1410cm -1 corresponds to Si-CH3, 1260 cm -1 , 1080cm -1 The peaks are Si-C and Si-O respectively; 3060-3020cm in the modified silicone resin curve -1 , 1600cm -1 The characteristic peak of -CH=CH2 at 2110cm -1 The Si-H characteristic peak appears at the bottom; the above results indicate the successful preparation of modified silicone resin.

[0028] The anticorrosive filler is prepared by the following preparation process: (a) Molybdenum powder, silicon powder, boron powder, and samarium powder were weighed in a mass percentage ratio of 95:4:1:1 and ball-to-material ratio of 15:1 under a nitrogen atmosphere and ball-milled for 24 h to obtain alloy powder. The alloy powder was heated to 1500°C at a rate of 5 min-1 under a vacuum of 0.010 Pa and sintered at a pressure of 40 MPa for 3 h. The temperature was then further increased to 1700°C, the pressure was reduced to 15 MPa, and the mixture was kept at this temperature for 3 h. The powder was then cooled in the furnace to obtain Mo-Si-B-Sm alloy powder. (b) The surface of the Mo-Si-B-Sm alloy powder was polished with 800#, 1500#, and 2000# sandpaper in sequence. The polished alloy surface was sandblasted with 36-mesh brown corundum sand shots using compressed air at an airflow pressure of 0.6 MPa for 12 s. After the sandblasting, the surface was ultrasonically cleaned with acetone and distilled water to obtain the treated Mo-Si-B-Sm alloy powder. (c) Al2O3 nanosheets, dopamine hydrochloride and Tris-HCl buffer (0.2 mol / L) with a pH of 8.5 were mixed in a ratio of 1 mg:1 mg:2 mL and ultrasonicated for 30 min to obtain a mixed solution. The treated Mo-Si-B-Sm alloy powder was added to the mixed solution in a ratio of 1 g:100 mL. The mixture was stirred for 10 h and then centrifuged. The solid product was washed with deionized water and ethanol, dried at 60°C, and then annealed in an argon atmosphere at 300°C for 1 h to obtain the above-mentioned anti-corrosion filler.

[0029] This embodiment also provides a method for preparing the lubricating coating for the surface of the alloy wire, which specifically comprises the following steps: adding the modified silicone resin according to the above-mentioned weight percentage to 50% of the solvent by mass, stirring at 600 rpm for 12 minutes to form a uniform resin solution, then sequentially adding molybdenum disulfide, NiFe2O4, and an anti-corrosion filler, and then adding wax slurry, BYK110, and the remaining solvent after stirring, and stirring at 1000 rpm for 18 minutes to achieve a uniform viscous state; finally, adding BYK354, and stirring at a low speed of 500 rpm for 8 minutes to obtain the lubricating coating for the surface of the alloy wire.

[0030] Example 2: Example 2 provides a lubricating coating for the surface of an alloy wire, comprising the following raw materials in percentage by weight: 13% modified silicone resin, 5% molybdenum disulfide, 2% NiFe2O4, 5% anti-corrosion filler, 2% bentonite, 1.5% BYK110, 1% BYK300, and the balance being a solvent prepared by mixing ethanol and isopropanol in a volume ratio of 7:3; The modified silicone resin is prepared by the following preparation process: (1) 1,3-dimethoxy-1,3-dimethyl-1,3-divinyldisiloxane, hydroxylated boron nitride and ethanol aqueous solution were added to an ethanol aqueous solution with a volume ratio of ethanol to water of 9:1 according to the ratio of 1 g:6 g:200 mL. The mixture was stirred at 60°C for 4 h, filtered, washed and dried to obtain intermediate 1. (2) Under nitrogen atmosphere, intermediate 1 and polymethylsilane were added to anhydrous toluene in a ratio of 1 g:1.5 g:100 mL, and the mixture was reacted at 110°C for 2 h. After the reaction, the modified silicone resin was obtained by vacuum distillation.

[0031] The anticorrosive filler is prepared by the following preparation process: (a) Molybdenum powder, silicon powder, boron powder, and samarium powder were weighed in a mass ratio of 90:5:2:3 and ball-milled for 20 h in a nitrogen atmosphere at a ball-to-material ratio of 10:1 to obtain alloy powder. The alloy powder was heated to 1400°C at a rate of 5 min-1 under a vacuum of 0.008 Pa and sintered at a pressure of 30 MPa for 2 h. The temperature was then further increased to 1700°C, the pressure was reduced to 10 MPa, and the mixture was kept at that temperature for 3 h. The powder was then cooled in the furnace to obtain Mo-Si-B-Sm alloy powder. (b) The surface of the Mo-Si-B-Sm alloy powder was polished with 800#, 1500#, and 2000# sandpaper in sequence. The polished alloy surface was sandblasted with 36-mesh brown corundum sand shots using compressed air at an airflow pressure of 0.5 MPa for 10 s. After the sandblasting, the surface was ultrasonically cleaned with acetone and distilled water to obtain the treated Mo-Si-B-Sm alloy powder. (c) Al2O3 nanosheets, dopamine hydrochloride and Tris-HCl buffer (0.2 mol / L) with a pH of 8.5 were mixed in a ratio of 1 mg:1.2 mg:2 mL, and ultrasonicated for 30 min to obtain a mixed solution. The treated Mo-Si-B-Sm alloy powder was added to the mixed solution in a ratio of 1 g:120 mL. The mixture was stirred for 10 h and then centrifuged. The solid product was washed with deionized water and ethanol, dried at 60°C, and then annealed in an argon atmosphere at 320°C for 1 h to obtain the above-mentioned anti-corrosion filler.

[0032] This embodiment also provides a method for preparing the aforementioned lubricating coating for the surface of an alloy wire, comprising the following specific steps: adding the modified silicone resin according to the aforementioned weight percentage to 50% of the solvent by mass, stirring at 500 rpm for 10 minutes to form a uniform resin solution, then sequentially adding molybdenum disulfide, NiFe2O4, and an anti-corrosion filler, and then adding bentonite, BYK110, and the remaining solvent after stirring, and stirring at 800 rpm for 15 minutes until the system reaches a uniform viscous state; finally, adding BYK300, and stirring at a low speed of 400 rpm for 5 minutes to obtain the aforementioned lubricating coating for the surface of an alloy wire.

[0033] Example 3: Example 3 provides a lubricating coating for the surface of an alloy wire, comprising the following raw materials in percentage by weight: 17% modified silicone resin, 8% molybdenum disulfide, 4% NiFe2O4, 8% anti-corrosion filler, 3% BYK320, 2% BYK110, 1% BYK354, and the balance being a solvent prepared by mixing ethanol and isopropanol in a volume ratio of 7:3; The modified silicone resin is prepared by the following preparation process: (1) 1,3-dimethoxy-1,3-dimethyl-1,3-divinyldisiloxane, hydroxylated boron nitride and ethanol aqueous solution were added to an ethanol aqueous solution with a volume ratio of ethanol to water of 9:1 according to the ratio of 1 g:8 g:250 mL. The mixture was stirred at 80°C for 6 h, filtered, washed and dried to obtain intermediate 1. (2) Under nitrogen atmosphere, intermediate 1 and polymethylsilane were added to anhydrous toluene in a ratio of 1 g:2 g:120 mL, and the mixture was reacted at 130°C for 4 h. After the reaction, the modified silicone resin was obtained by vacuum distillation.

[0034] The anticorrosive filler is prepared by the following preparation process: (a) Molybdenum powder, silicon powder, boron powder, and samarium powder were weighed in a mass ratio of 97:2:0.5:0.5 and ball-milled under a nitrogen atmosphere at a ball-to-material ratio of 20:1 for 30 h to obtain an alloy powder. The alloy powder was heated to 1600°C at a rate of 5 min-1 under a vacuum of 0.015 Pa and sintered at a pressure of 50 MPa for 5 h. The temperature was then further increased to 1800°C, the pressure was reduced to 20 MPa, and the mixture was kept at this temperature for 3 h. The powder was then cooled in the furnace to obtain Mo-Si-B-Sm alloy powder. (b) The surface of the Mo-Si-B-Sm alloy powder was polished with 800#, 1500#, and 2000# sandpaper in sequence. The polished alloy surface was sandblasted with 36-mesh brown corundum sand shots using compressed air at an airflow pressure of 0.8 MPa for 15 s. After the sandblasting, the surface was ultrasonically cleaned with acetone and distilled water to obtain the treated Mo-Si-B-Sm alloy powder. (c) Al2O3 nanosheets, dopamine hydrochloride and Tris-HCl buffer (0.2 mol / L) with a pH of 8.5 were mixed in a ratio of 1 mg:1.2 mg:2.5 mL and ultrasonicated for 30 min to obtain a mixed solution. The treated Mo-Si-B-Sm alloy powder was added to the mixed solution in a ratio of 1 g:150 mL. The mixture was stirred for 12 h and then centrifuged. The solid product was washed with deionized water and ethanol, dried at 60°C, and then annealed in an argon atmosphere at 350°C for 1.5 h to obtain the above-mentioned anti-corrosion filler.

[0035] This embodiment also provides a method for preparing the aforementioned lubricating coating for the surface of an alloy wire, comprising the following specific steps: adding the modified silicone resin according to the aforementioned weight percentage to 60% of the solvent by mass, stirring at 800 rpm for 15 minutes to form a uniform resin solution, then sequentially adding molybdenum disulfide, NiFe2O4, and an anti-corrosion filler, and then adding BYK320, BYK110, and the remaining solvent after stirring, and stirring at 1000 rpm for 20 minutes to achieve a uniform viscous state; finally, adding BYK354, and stirring at a low speed of 600 rpm for 10 minutes to obtain the aforementioned lubricating coating for the surface of an alloy wire.

[0036] (2) Comparative Example Comparative Example 1: Comparative Example 1 is substantially the same as Example 1, except that the modified silicone resin is replaced by a physical mixture of polymethylsilane and hydroxylated boron nitride.

[0037] Comparative Example 2: Comparative Example 2 is substantially the same as Example 1, except that step (c) of preparing the anti-corrosion filler is omitted, that is, the anti-corrosion filler is replaced by the treated Mo-Si-B-Sm alloy powder.

[0038] Comparative Example 3: Comparative Example 3 is substantially the same as Example 1, except that the samarium powder in step (a) of preparing the anti-corrosion filler is replaced by yttrium powder, i.e., the Mo-Si-B-Sm alloy powder in step (b) is replaced by Mo-Si-BY alloy powder.

[0039] Comparative Example 4: Comparative Example 4 is basically the same as Example 1, except that step (c) of preparing the anti-corrosion filler is omitted, and the Mo-Si-B-Sm alloy powder and the Al2O3 nanosheets are directly physically mixed, that is, the anti-corrosion filler is replaced by a physical mixture of Mo-Si-B-Sm alloy powder and alumina.

[0040] (3) Test examples The lubricating coatings of Examples 1-3 and Comparative Examples 1-4 were sprayed on the surface of GH2909 alloy test pieces respectively with a spraying thickness of 50 μm. After heating and curing at 200° C. for 2 h, a lubricating coating protective coating was formed.

[0041] Impact resistance: According to GB / T 1732-2020 “Determination of impact resistance of paint films”, the impact resistance of the lubricating coatings of Examples 1-3 and Comparative Examples 1-4 was tested. The results are shown in Table 1.

[0042] Wear resistance: The wear resistance of the lubricating coatings of Examples 1-3 and Comparative Examples 1-4 was tested in accordance with GB / T 12444-2006, Metallic Materials Wear Test Methods - Test Ring-Test Block Sliding Wear Test, with a load of 20 N, a reciprocating frequency of 5 Hz, a friction length of 4 mm, and a wear time of 30 min. The results are shown in Table 1.

[0043] Flexibility: According to GB / T 1731-2020 “Determination of flexibility of paint films and putty films”, the flexibility of the lubricating coatings of Examples 1-3 and Comparative Examples 1-4 was tested. The results are shown in Table 1.

[0044] High temperature corrosion performance: According to HB 5258-2000 “Test method for determination of oxidation resistance of steel and high temperature alloys”, the oxidation performance of Examples 1-3 and Comparative Examples 1-4 was tested at an experimental temperature of 800°C. The results are shown in Table 1.

[0045] Table 1 Wear resistance, flexibility and high temperature corrosion test results of lubricating coatings Group Impact resistance (cm) <![CDATA[Wear rate (mm 3 / N·m)]]> Flexibility (mm) <![CDATA[Oxidation rate (g / m 2 ·h)]]> Example 1 50 <![CDATA[3.12×10 -7 ]]> 1 0.06 Example 2 50 <![CDATA[3.83×10 -7 ]]> 1 0.07 Example 3 50 <![CDATA[4.02×10 -7 ]]> 1 0.09 Comparative Example 1 45 <![CDATA[9.55×10 -7 ]]> 2 0.14 Comparative Example 2 50 <![CDATA[6.58×10 -7 ]]> 1 0.29 Comparative Example 3 50 <![CDATA[6.81×10 -7 ]]> 1 0.17 Comparative Example 4 50 <![CDATA[5.34×10 -7 ]]> 1 0.23 As shown in Table 1, the lubricating coatings prepared in Examples 1-3 of the present invention exhibit excellent mechanical properties and outstanding chemical corrosion resistance when applied to alloy surfaces. Compared to Example 1, Comparative Example 1 replaces the modified silicone resin with a physical mixture of polymethylsilane and hydroxylated boron nitride; Comparative Example 2 replaces the anti-corrosion filler with treated Mo-Si-B-Sm alloy powder; Comparative Example 3 replaces the Mo-Si-B-Sm alloy powder in step (b) with Mo-Si-BY alloy powder; and Comparative Example 4 replaces the anti-corrosion filler with a physical mixture of Mo-Si-B-Sm alloy powder and alumina. The wear resistance, flexibility, and high-temperature corrosion resistance of Comparative Examples 1-4 are all reduced. A detailed analysis reveals that, on the one hand, the modified silicone resin prepared by the present invention through the organosilicon-boron nitride hybrid crosslinking network exhibits excellent high-temperature resistance (>800°C), significantly improving the wear resistance and mechanical properties of the coating. The present invention uses high-temperature resistant hydroxylated boron nitride as raw material, utilizes the condensation reaction of its surface hydroxyl groups with 1,3-dimethoxy-1,3-dimethyl-1,3-divinyldisiloxane to form stable Si-OB covalent bonds and introduces active double bonds, so that h-BN is uniformly dispersed and anchored in the polymer network, giving the resin high-temperature resistance and avoiding interface defects caused by filler agglomeration; then, through the silicon hydrogen addition reaction of the introduced double bonds with the Si-H bonds in polymethylsilane, a high cross-linking density network structure is constructed, and the generated flexible Si-CH2-CH2-Si chain segments cooperate with Si-O-Si chains to improve the mechanical properties and wear resistance of the coating. Under the action of dynamic load, the flexible chain segments absorb friction energy through conformational changes, while the interlayer slip effect of the h-BN nanosheets further dissipates stress, effectively inhibiting crack initiation and expansion. On the other hand, the present invention also adds Mo-Si-B-Sm-based anti-corrosion fillers, which can improve the high-temperature oxidation corrosion resistance of the coating. The present invention adds the rare earth element Sm to the Mo-Si-B alloy. The addition of Sm further refines the grain size and increases the material density. During high-temperature oxidation, Sm generates Sm2O3, which forms a Sm-Si-BO composite glass phase with SiO2 / B2O3, effectively blocking oxygen diffusion. After multi-stage grinding and sandblasting, the Mo-Si-B-Sm alloy powder forms a uniformly roughened surface, significantly increasing the specific surface area and the number of active sites. Furthermore, through the in-situ polymerization reaction of polydopamine, Al2O3 nanosheets adhere to form a densely packed continuous layer, effectively blocking the penetration of corrosive media and slowing chemical corrosion of the substrate.

[0046] Finally, it should be noted that the above embodiments are intended only to illustrate the technical solutions of the present invention and are not intended to limit the same. The basic principles and main features of the present invention have been described above using specific implementation schemes. Modifications or substitutions may be made based on the present invention, but such modifications or substitutions do not detract from the essence of the corresponding technical solutions from the scope of protection claimed by the present invention.

Claims

1. A lubricating coating for the surface of an alloy wire, characterized in that: The invention is composed of the following raw materials in percentage by weight: 13-17% modified silicone resin, 5-8% molybdenum disulfide, 2-4% NiFe2O4, 5-8% anti-corrosion filler, 2-3% thixotropic agent, 1.5-2% dispersant, 0.5-1% leveling agent, and the balance is solvent; The modified silicone resin is prepared by the following preparation process: (1) Add 1,3-dimethoxy-1,3-dimethyl-1,3-divinyldisiloxane and hydroxylated boron nitride to an ethanol aqueous solution, stir to react, filter, wash, and dry to obtain intermediate 1; (2) In an inert gas atmosphere, polymethylsilane and intermediate 1 are added to anhydrous toluene, heated for reaction, and after the reaction is completed, the modified silicone resin is obtained by vacuum distillation.

2. The lubricating coating for alloy wire surface according to claim 1, characterized in that: The structural formula of the intermediate 1 in step (1) is .

3. The lubricating coating for alloy wire surface according to claim 1, characterized in that: In step (1), the mass ratio of 1,3-dimethoxy-1,3-dimethyl-1,3-divinyldisiloxane to hydroxylated boron nitride is 1:(6-8); the stirring reaction temperature is 60-80° C., and the time is 4-6 hours.

4. The lubricating coating for alloy wire surface according to claim 1, characterized in that: In step (2), the mass ratio of the intermediate 1 to polymethylsilane is 1:(1.5-2); the heating reaction temperature is 110-130° C., and the time is 2-4 hours.

5. The lubricating coating for alloy wire surface according to claim 1, characterized in that: The anticorrosive filler is prepared by the following preparation process: (a) Molybdenum powder, silicon powder, boron powder, and samarium powder are ball-milled in an inert gas atmosphere to obtain alloy powder. The alloy powder is pressure-sintered in a vacuum, depressurized, maintained, and cooled to obtain Mo-Si-B-Sm alloy powder; (b) grinding the surface of the Mo-Si-B-Sm alloy powder, sandblasting, ultrasonic cleaning, and drying to obtain treated Mo-Si-B-Sm alloy powder; (c) adding dopamine hydrochloride and Al2O3 nanosheets to a Tris-HCl buffer solution and ultrasonically dispersing the mixture to obtain a mixed solution, immersing the treated Mo-Si-B-Sm alloy powder in the mixed solution, stirring, centrifuging, washing, drying, and then annealing in an argon atmosphere to obtain the anti-corrosion filler.

6. The lubricating coating for alloy wire surface according to claim 5, characterized in that: The mass ratio of molybdenum powder, silicon powder, boron powder and samarium powder in step (a) is (90-97): (2-5): (0.5-2): (0.5-3); the pressure sintering temperature is 1400-1600°C, the pressure is 30-50 MPa, and the time is 2-5 hours; the pressure reduction and heat preservation temperature is 1700-1800°C, the pressure is 10-20 MPa, and the time is 2-3 hours.

7. The lubricating coating for alloy wire surface according to claim 5, characterized in that: The air flow pressure of the sandblasting treatment in step (b) is 0.5-0.8 MPa, and the time is 10-15 seconds; the mass ratio of Al2O3 nanosheets to dopamine hydrochloride in step (c) is 1:(1-1.2); the amount ratio of the treated Mo-Si-B-Sm alloy powder to the mixed solution is 1g:100-150mL; the annealing temperature is 300-350°C, and the time is 1-1.5h.

8. The method for preparing a lubricating coating for an alloy wire surface according to claim 1, wherein: The thixotropic agent is any one of wax slurry, bentonite or BYK320; the leveling agent is BYK354 or BYK300; the dispersant is BYK110; and the solvent is a mixed solution of ethanol and isopropyl alcohol.

9. The method for preparing the lubricating coating for the surface of the alloy wire according to any one of claims 1 to 8, characterized in that: The following steps are involved: According to the weight percentage, the modified silicone resin is added to 50-60% of the solvent mass and stirred to form a resin solution, and then molybdenum disulfide, NiFe2O4 and anti-corrosion filler are added in sequence. After stirring, a thixotropic agent, a dispersant and the remaining solvent are added, and finally a leveling agent is added and stirred to obtain the lubricating coating.

Citation Information

Patent Citations

  • Modified boron nitride grafted waterborne acrylic resin insulating material and preparation method thereof

    CN111484626A

  • Nano boron nitride grafted acrylic resin insulating material and preparation method thereof

    CN111848887A

  • High-temperature-resistant oil-resistant organic-inorganic hybrid epoxy composite wear-resistant lubricating coating and preparation method thereof

    CN116333557A

  • Single-component root puncture resistant waterproof paint and preparation method therefor

    WO2021022925A1